High Reliability for Weightbearing CT Based Automated 3D Measurements to Assess Progressive Collapsing Foot Deformity. Issue 1 (January 2022) - Kvarda, Peter; Krähenbühl, Nicola; Susdorf, Roman; Burssens, Arne; Ruiz, Roxa; Barg, Alexej; Hintermann, Beat
Category: Hindfoot; Midfoot/Forefoot; Other Introduction/Purpose: In progressive collapsing foot deformity (PCFD), hind- and midfoot deformities are paramount. However, an accurate assessment thereof, using weightbearing radiography, remains challenging. Automated three-dimensional (3D) measurements derived from weightbearing computed tomography (WBCT) scans may provide a more accurate approach for deformity assessment. In this study, automated 3D measurements based on WBCT were compared to two-dimensional (2D) measurements performed on weightbearing radiographs. Furthermore, it was investigated whether various stages of PCFD could be identified using automated 3D measurements. Methods: Twenty patients treated at our institution with either a flexible (N=10) or rigid (N=10) PCFD were identified, retrospectively analyzed and compared to a control group of thirty healthy individuals. Four angles and two distances measured on weightbearing radiographs were compared to the automated 3D measurements derived from WBCT scans. Results: In 5 out of 6 variables, the reliability of the measurements derived from weightbearing radiographs was lower than the automated measurements that derived from WBCT scans. The automated 3D measurements showed: the talar tilt in the ankle mortise was more valgus in patients with a rigid PCFD when compared to patients with a flexible PCFD; medial facet subluxation was present in all but one patient; patients with a sinus tarsi impingement evidenced a higher overlap between the talus and calcaneus (12.4+-2.6 mm) compared to patients without impingement (7.8+-3.9 mm; P=0.020). Conclusion: A higher reliability of automated 3D measurements derived from WBCT scans, was evident for most variables when compared to measurements based on weightbearing radiographs. Besides being less prone to errors, automated 3D measurements may provide more reliable information regarding the hind- and midfoot alignment in patients with PCFD. Future studies may show to what extent 3D measurements could contribute to current diagnostic algorithms and treatment concepts of patients with PCFD.